A Region in the Bacillus subtilis Transcription Factor Spo0A That Is Important for spoIIG Promoter Activation - Buckner, Cindy M. (American Society for Microbiology, 1998)
Spo0A is a DNA binding protein in Bacillus subtilis required for the activation of spoIIG and other promoters at the onset of endospore formation. Activation of some of these promoters may involve interaction of Spo0A and the ς(A) subunit of RNA polymerase. Previous studies identified two single-amino-acid substitutions in ς(A), K356E and H359R, that specifically impaired Spo0A-dependent transcription in vivo. Here we report the identification of an amino acid substitution in Spo0A (S231F) that suppressed the sporulation deficiency due to the H359R substitution in ς(A). We also found that the S231F substitution partially restored use of the spoIIG promoter by the ς(A) H359R RNA polymerase in vitro. Alanine substitutions in the 231 region of Spo0A revealed an additional amino acid residue important for spoIIG promoter activation, I229. This amino acid substitution in Spo0A did not affect repression of abrB transcription, indicating that the alanine-substituted Spo0A was not defective in DNA binding. Moreover, the alanine-substituted Spo0A protein activated the spoIIA promoter; therefore, this region of Spo0A is probably not required for Spo0A-dependent, ς(H)-directed transcription. These and other results suggest that the region of Spo0A near position 229 is involved in ς(A)-dependent promoter activation.